Gothic death 1740-1914 : a literary history - Smith, Andrew, 1964- (Manchester Gothic (Manchester, England), 2016)
Drawing on a range of popular Gothic and Victorian novels, poems and short stories, this book provides the first full length study of representations of death and dying in Gothic texts between 1740 and 1914.